AKSESIBILITAS PENYANDANG TUNADAKSA - Utami, Ezza Oktavia; Raharjo, Santoso Tri; Apsari, Nurliana Cipta (Prosiding Penelitian dan Pengabdian kepada Masyarakat, 2018)
AbstractAccessibility is a component of the implementation of inclusive Education that must be met. Aiming to facilitate students with disabilities to do mobility and access on campus, so that students with disabilities can perform activities independently without any obstacles and constraints of its diffability. The existence of accessibility to the building of inadequate educational institutions creates a barrier for persons with disabilities. Accessibility in this study focused on the accessibility of people with physically disabled by taking the case of buildings located at the Bandung Institute of Technology (ITB) located in Jatinangor. The data collection method used is physical field observation, literature study taken from textbook, article, and internet exploration. The final conclusion shows that accessibility of institutional buildings still has not reached perfectly in accordance with existing standards to be accessible to persons with disabilities and not yet fulfilling accessibility principles; safety, convenience, usability, independence. However, some buildings have tried to present the elements of accessibility that is sufficient to provide convenience for the disabled as a user of the building.Abstrak Askesibilitas merupakan suatu komponen dari pelaksanaan Pendidikan inklusi yang harus dipenuhi. Bertujuan untuk memudahkan mahasiswa difabel untuk melakukan mobilitas dan akses yang ada di kampus, agar mahasiswa difabel dapat melakukan aktifitas secara mandiri tanpa hambatan dan kendala-kendala difabilitasnya. Keberadaan aksesibilitas pada bangunan institusi pendidikan yang belum memadai menimbulkan hambatan tersendiri bagi penyandang disabilitas. Aksesibilitas dalam kajian ini difokuskan kepada aksesibilitas pada penyandang Tunadaksa dengan mengambil kasus bangunan yang terdapat di Institut Teknolgi Bandung (ITB) yang berlokasi di Jatinangor. Metode pengambilan data yang digunakan adalah dengan observasi lapangan fisik, studi literatur yang diambil dari buku teks, artikel, dan penjelajahan internet. Hasil riset menunjukkan bahwa aksesibilitas bangunan institusi masih belum mencapai sempurna sesuai dengan standar yang ada untuk dapat diakses oleh penyandang tunadaksa serta belum memenuhi asas aksesibilitas; keselamatan, kemudahan, kegunaan, kemandirian. Namun, sebagian bangunan telah berusaha menghadirkan elemen-elemen aksesibilitas yang cukup memberikan kemudahan bagi penyandang Tunadaksa sebagai pengguna bangunan.Â